Rethinking maker education: makerspaces, gender, and STEM skills in the era of inclusive educational intelligence - George-Reyes, Carlos Enrique; Tapia-Bastidas, Tatiana; Sandoval-Benitez, Luisa Fernanda; Caicedo-Quiroz, Rosangela; Pinto-Santos, Alba Ruth (Frontiers in Education, 2025)
Maker education has emerged as an innovative pedagogical approach that promotes active learning through creation, collaboration, and technological experimentation. This study analyzed the conceptual evolution, beneficiary groups, access barriers, and STEM skills developed within makerspaces, with special attention to gender equity and educational sustainability. A systematic literature review was conducted in Scopus and Web of Science following the PRISMA protocol, including 202 documents published between 1983 and 2025, processed using R software and Zotero to identify trends, authors, themes, and theoretical gaps. The findings show a sustained increase in scientific production since 2015, a transformation of makerspaces into hybrid physical-virtual ecosystems, and an expansion of beneficiaries to more diverse communities. Although structural and cultural barriers continue to limit female participation, inclusive models mediated by artificial intelligence and design thinking are emerging. It can be stated that Maker education is evolving toward an interdisciplinary, ethical, and equitable paradigm, providing evidence of its potential to democratize innovation and strengthen STEM competencies with a social focus, while also identifying theoretical gaps related to the lack of integrative evaluative models and longitudinal studies that measure its sustainable impact.